Tax aggressiveness and profitability in companies in the electric power sector in Brazil - Santos, Daniel Gomes dos (2020)
This study aimed to analyze the influence of tax aggressiveness on the ability to generate profit in companies in the electric power sector listed in B3 in the period from 2013 to 2018. This is descriptive, quantitative, documentary and bibliographic research. The sample includes 37 companies during the period studied, forming a total of 222 observations. BTD (Book Tax Differences) and GAAP ETR (Generally Accepted Accounting Principles, Effective Tax Rate) were used as a metric for tax aggressiveness and NM (Net Margin), ROA (Return on Assets) and ROI (Return on Investment) as indicators of profitability. The results were achieved by means of descriptive statistics of the data, linear regression analysis, in which a panel model with random effects was applied, and quantile regression analysis. With the result it was found that, in general, the higher the level of tax aggressiveness, the higher the profitability indexes. This study aims to contribute to companies in the electric power sector to verify the efficiency of the use of aggressive tax planning, supporting decision making.